Ten-dimensional hyphenation including simulated static gastro-intestinal digestion on the adsorbent surface, planar assays, and bioactivity evaluation for meal replacement products. Issue 1 (13th December 2022) - Schreiner, Tamara; Eggerstorfer, Naila Margot; Morlock, Gertrud Elisabeth
Abstract : Evaluation of the bioactivity of meal replacement products before and after gastrointestinal digestion using a ten-dimensional bioanalytical hyphenation. Abstract : Meal replacement products are normally consumed in weight-loss interventions and the treatment of obesity and diabetes. Changing lifestyles and eating habits made meal replacement products in the forms of shakes and bars a good alternative as To-go-meals, promoted as balanced in its composition and thus healthier compared to other ready-to-eat meals. This study aimed to evaluate the bioactivity of six differently flavoured powdered meal replacement products. Their analysis was made by a ten-dimensional hyphenation composed of digestion on the adsorbent surface, followed by normal-phase high-performance thin-layer chromatographic separation, multi-imaging, and planar assay application (effect-directed analysis), and then heart-cut elution/transfer of bioactive compound zones to reversed-phase high-performance liquid chromatography, diode array detection, and high-resolution tandem mass spectrometry. The on-surface digestion of saccharides, fats, and proteins through intestinal enzymatic activity revealed new breakdown products. These exhibited bioactivity in their different effect-profiles obtained by the Gram-negative Aliivibrio fischeri bioassay as well as α-/β-glucosidase and acetyl-/butyrylcholinesterease inhibition assays. The main bioactive compounds arising through simulated static pancreatic digestion were saturated and unsaturated free fatty acids. The synthetic sweetener sucralose was not influenced by simulated static intestinal digestion, but showed antimicrobial activity. In the prepared drinking meals with coffee and choco flavour, the acetylcholinesterase-inhibiting methylxanthines caffeine and theobromine were identified as bioactive compounds. Some other bioactive constituents could not be assigned to specific molecules and require further analyses. Although the studied meal replacement products showed health-beneficial properties through antimicrobial properties or inhibition of enzymes involved in the expression of the civilisation diseases, such as diabetes and Alzheimer's disease, plant foods, herbs and spices have been shown to be even richer and more versatile in bioactive compounds.